WISMA ATLET PENYANDANG CACAT DI SURAKARTA - Leni Pramudianto, Yuli, Ir. Nurhasan, MT (2016)
Appears an assumption in society that people with disabilities can not do anything amid limitations. God created man in the middle there is an excess kekurangaanya definitely one of them in the field of sports. Many people with disabilities that have the potential and excel in sport by becoming athletes. Still the lack of supply of container for the coaching and training of athletes - alet disabled people in Indonesia can hinder the progress of the athletes. In Indonesia there is no Breakfast at designated for Athletes with disabilities. Provision Pensions Athletes for Athletes with disabilities is in need so that athletes across Indonesia can be focused to practice in one place and NPC Indonesia as an official organization that houses athletes - athletes penyanang disability in Indonesia is easier to build, improve performance, coordinate, provide protection and fostering the welfare of the athlete. Surakarta themselves are not familiar anymore with athletes with disabilities, are like in 2011 Surakarta to host the Games Asean Para Games (APG), hosted Pesata Sports Handicapped National level (Peparnas) and also the concentration of athletes with disabilities to practice in Surakarta and in Colomadu PPRBM Building and Wisma Yayasan Insan Sembada (YIS) Karangasem as a temporary dormitory for athletes stay. In particular there is no place to stay and train athletes. Given the number of athletes with disabilities the activities mentioned in the report, the city of Surakarta can be made in one of the cities in Indonesia for Athletes with disabilities concentration with the construction of Wisma Athletes with disabilities.